Does the fellow‐villager relationship between the independent director and the chairman of the board can inhibit the major shareholder expropriation? Evidence from China. (4th June 2021) - Yu, Yike; Cao, Danting; Wang, Zuogong; Zhang, Zaijie
Abstract : We studied the influence of the fellow‐villager relationship between the independent directors and the chairman of the board and found that the above relationship significantly eased the shareholder's encroachment. Furthermore, the above suppression effect is more significant in the poor formal institutional environment, and higher equity balance will weaken the restraining effect. At last, we revealed that the reputation mechanism presented the key factor that urged independent directors to exert influence on the decision of the chairman through the fellow‐villager relationship and, in turn, inhibited the encroachment.